Utilizing of Augmented Reality (AR)-Based Flashcards Media on Increasing Vocabulary and Language Understanding in Early Children - Eges Triwahyuni; Pascalian Hadi Pradana (Journal of Sustainable Educational Technology and Innovation, 2025)
Background of study: Utilizing contemporary technology in the classroom has many advantages in the field of early childhood education. The usage of Flashcards based on Augmented Reality (AR) is one of the most recent breakthroughs. this approach can significantly enhance learning engagingly and enjoyably.Aims and scope of paper: The purpose of this study is to investigate an effect after applying AR based flashcards on language development in early childhood.Methods: Participants This study was conducted as a quantitative experimental method one group pretest–posttest design, and 14 children were included in the analysis. Data analysis was performed with one-sample t-tests.Result: The result show that the avarege pre-test (Before treatment) language ability of 11.21 was statistically much lower than the test score (20), t value = -27.664, P value=0.000. The item mean score at posttest was 22.21, which was significantly higher than the test score (t = 4.387, p-value = 0.001). There was a significant difference before and after therapy, according to the 95% confidence interval (CI). These findings suggest that using flashcards based on augmented reality can effectively enhance children's language abilities. This notable distinction suggests that flashcards based on augmented reality successfully enhance kids' vocabulary acquisition.Conclusion: Thus, this study comes to the conclusion that flashcards based on augmented reality (AR) have a beneficial effect on the vocabulary acquisition of young children, making them a promising new learning aid for enhancing language proficiency. According to the study's findings, early childhood vocabulary and language understanding are greatly enhanced by augmented reality (AR)-based flashcards.